$\begin{array}{1 1}(x-3)^2+(y+4)^2=45^2\\(x-3)^2+(y+4)^2=\large\frac{\sqrt{45}}{13}\\(x-3)^2+(y+4)^2=\big(\large\frac{45}{13}\big)^2\\(x-3)^2+(y+4)^2=\sqrt{\large\frac{45}{13}}\end{array} $

Answer

Comment

Share

Q)

[Hint : To determine radius find the perpendicular distance from the centre of the circle to the line.]

$\begin{array}{1 1}(x-3)^2+(y+4)^2=45^2\\(x-3)^2+(y+4)^2=\large\frac{\sqrt{45}}{13}\\(x-3)^2+(y+4)^2=\big(\large\frac{45}{13}\big)^2\\(x-3)^2+(y+4)^2=\sqrt{\large\frac{45}{13}}\end{array} $

Clay6 tutors use Telegram^{*} chat app to help students with their questions and doubts.

Do you have the Telegram chat app installed?

...